Management of common running injuries - Strakowski, J. A.; Jamil, T. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
Summary: Runners are susceptible to a variety of potential injuries because of the considerable stress of this activity. This can create a challenge for the treating practitioner; however, many of the common ailments occur in a reasonably predictable pattern. A careful history and physical examination are necessary for accurate diagnosis. Having a good understanding of these injuries as well of the role of biomechanical factors and common training errors can assist with appropriate care. Further development in the knowledge of soft tissue trauma, gait, and diagnostic and therapeutic modalities should lead to improved management of the injuries facing these athletes.